Tourism Promotion Efforts Between Challenges and Prospects: Case Study of the Wilaya of Mila - بوعروج لمياء (Finance and Business Economies Review, 2023)
This study aims to examine tourism promotion efforts in the wilaya of Mila , the developments of completed tourism projects, the challenges they face, and future prospects , as it has many tourism potentials that can accelerate its development process . The study reached the conclusion that the efforts exerted in general are weak and that they do not up to par with what fits the existing potentials, as well as the presence of a number of obstacles, on top of which are administrative problems and weak funding.